Peran Guru Pendidikan Agama Islam dalam Pembinaan Akhlak Siswa di MTs Muhammadiyah Blimbing Kabupaten Sukoharjo - Nurul Lutfiah Hilalyani; Muhammad Ja’far Nashir; Herri Gunawan (STIT Sirojul Falah Bogor, 2025)
The purpose of this study was to determine how the role of Islamic religious education teachers in fostering student morals at MTs Muhammadiyah Blimbing Sukoharjo Regency. This type of research is descriptive qualitative research. This research took place at MTs Muhammadiyah Blimbing Sukoharjo Regency. The results of this study are the role of Islamic religious education teachers in fostering student morals, among others, with the school program provided for the creation of moral guidance to students including the holding of the 5S program, the provision of positive activities (spiritual inspiration) which is done every friday in two weeks, the adjustment of learning materials including the use of appropriate learning methods.